Consuming yellow pea fiber reduces voluntary energy intake and body fat in overweight/obese adults in a 12-week randomized controlled trial. Issue 1 (February 2017) - Lambert, Jennifer E.; Parnell, Jill A.; Tunnicliffe, Jasmine M.; Han, Jay; Sturzenegger, Troy; Reimer, Raylene A.
Summary: Background & aims: The purpose of this randomized, double-blind, placebo-controlled study was to assess the effects of yellow pea fiber intake on body composition and metabolic markers in overweight/obese adults. Methods: Participants (9 M/41 F; age 44 ± 15 y, BMI 32.9 ± 5.9 kg/m 2 ) received isocaloric doses of placebo (PL) or pea fiber (PF; 15 g/d) wafers for 12 weeks. Outcome measures included changes in anthropometrics, body composition (DXA), oral glucose tolerance test (OGTT), food intake ( ad libitum lunch buffet), and biochemical indices. Results: The PF group lost 0.87 ± 0.37 kg of body weight, primarily due to body fat (−0.74 ± 0.26 kg), whereas PL subjects gained 0.40 ± 0.39 kg of weight over the 12 weeks (P = 0.022). The PF group consumed 16% less energy at the follow-up lunch buffet (P = 0.026), whereas the PL group did not change. During the OGTT, glucose area under the curve (AUC) was lower in PF subjects at follow-up (P = 0.029); insulin increased in both groups over time (P = 0.008), but more so in the PL group (38% higher AUC vs. 10% higher in the PF group). There were no differences in gut microbiota between groups. Conclusions: In the absence of other lifestyle changes, incorporating 15 g/day yellow pea fiber may yield small but significant metabolic benefits and aid in obesity management. Clinical Trial Registry : ClinicalTrials.gov NCT01719900.